The Association of Pornographic Media Exposure and Nutritional Status with Early Menarche - Deswita Deswita; Randy Refnandes; Mella Gustriyani Putri (Universitas Airlangga, 2018)
Introduction: The adolescent menarche period has shifted to a younger age because of several factors, including a girl’s nutritional status and exposure to pornographic media. The purpose of this study is to determine the relationship between pornographic media exposure and nutritional status with the age of menarche in girls in elementary school.Methods: This research used a descriptive cross-sectional design. 121 respondents were selected by proportional random sampling. Nutritional status data was collected by measuring body mass index, while the usage of media exposure and the age of menarche were both identified using questionnaires. All data was analysed using the chi-square test.Results: There was a significant relationship between the age of menarche with the exposure to mass media (p=0.000) and nutritional status (p=0.000).Conclusion: The age of menarche in adolescent girls is associated with nutritional status and media exposure.